2013
DOI: 10.1111/nmo.12221
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitor responders who are not confirmed as GERD patients with impedance and pH monitoring: who are they?

Abstract: In a substantial subgroup of patients responding to PPI with typical reflux symptoms, the diagnosis of GERD cannot be confirmed with pH-impedance monitoring. Proton pump inhibitor response and presence of typical symptoms are thus not reliable predictors of the diagnosis and antireflux surgery should always be preceded by reflux monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 40 publications
1
60
0
5
Order By: Relevance
“…1, it is interesting that[50 % of the patients who had been prescribed a PPI after a negative test experienced a clinical improvement. In our view, it is possible that the patients had GER disease and the test was falsely negative, or they did not have GER disease, i.e., they either had a functional disorder or their symptoms had a different cause, and their improvement was related to the reassurances of their attending physician and the placebo effect of PPIs [25]. It has been previously reported that placebo and PPIs have a similar effect in patients with signs and/or symptoms of chronic posterior laryngitis [26].…”
Section: Discussionmentioning
confidence: 85%
“…1, it is interesting that[50 % of the patients who had been prescribed a PPI after a negative test experienced a clinical improvement. In our view, it is possible that the patients had GER disease and the test was falsely negative, or they did not have GER disease, i.e., they either had a functional disorder or their symptoms had a different cause, and their improvement was related to the reassurances of their attending physician and the placebo effect of PPIs [25]. It has been previously reported that placebo and PPIs have a similar effect in patients with signs and/or symptoms of chronic posterior laryngitis [26].…”
Section: Discussionmentioning
confidence: 85%
“…5,6 In addition, the response to proton pump inhibitors (PPIs) has limited the ability to identify gastroesophageal reflux disease (GERD) patients. [7][8][9] Recently, it was suggested that low esophageal basal impedance measurements may reflect the status of the esophageal mucosa and thus may be used to study the role of the impaired mucosal integrity and increased acid sensitivity in patients with heartburn. [10][11][12] According to previous findings, baseline impedance levels may be useful to increase the diagnostic sensitivity of MII-pH monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms were evaluated both before and after therapy through a validated questionnaire (GERD Impact Scale [GIS]) and a visual analogue scale (VAS) for heartburn as previously described. 8 Then, all subjects underwent stationary esophageal manometry and 24-hour MII-pH off-therapy (14-day wash-out). Patients were allowed to take only alginates, on an as-needed basis, as rescue therapy for controlling heartburn.…”
Section: Methodsmentioning
confidence: 99%
“…Severity of dysphagia, heartburn, regurgitation, and chest pain was measured on a VAS (0–100). The VAS score has been adopted in many other trials for evaluation of visceral symptoms and has been used as a tool for self-assessment of symptoms [11, 12], and any decrease in the score at week 4 versus baseline was considered an improvement. Demographic data and phenotypic characteristics of the disease were collected from the clinical charts.…”
Section: Methodsmentioning
confidence: 99%